Simulation of Cellular Network Model by Integer Programming - Agustina Pradjaningsih (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
Integer programming is a particular form or variety of the linear program, in which one or more of its values in the solution vector have integer. Integer programming can be applied on the network analysis and telecommunication. In this paper, integer programming is used to solve the problems of optimizing the route between cell i and HUB (Home Unit Base) j so that the cost for making a network model, especially cellular network, can be minimized.